Beyond slavery: overcoming its religious and sexual legacies - Brooten, Bernadette J.; Hazelton, Jacqueline L. (Black religion, womanist thought, social justice, 2010)
This book looks at a United States that continues to be driven by racial and cultural divisions, from the disproportionately high number of incarcerated African Americans to heartfelt disagreements over the true nature of marriage and the proper role of faith in public policy.